Taking Center Stage - Gautam Borah (2018)
"In an article columns, Chuck Wall, founder and chief executive officer of Marketpower Group spoke about how too many companies are relying exclusively on data to explain what customers really need. Ironically many have too much data to process and make actionable."
Keywords: Management